1997
DOI: 10.1172/jci119619
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces heat-shock protein 70 expression in vascular smooth muscle cells via activation of heat shock factor 1.

Abstract: Current data suggest that nitric oxide (NO) is a doubleedged sword that could result in relaxation and/or cytotoxicity of vascular smooth muscle cells (SMCs) via cGMPdependent or -independent signal pathways. Stress or heat shock proteins (hsps) have been shown to be augmented in arterial SMCs during acute hypertension and atherosclerosis, both conditions that are believed to correlate with disturbed NO production. In the present study, we demonstrate that NO generated from sodium nitroprusside (SNP), S -nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 71 publications
11
79
2
1
Order By: Relevance
“…In the present study the observed upregulation of HSP 70-1A and -1B is consistent with a previous report showing NO inducing HSP 70 expression in SMC's via HSF 1 activation [27]. It is thought that the upregulation of HSP 70 is to protect the SMC's from injury as a result of NO stimulation [27].…”
Section: Adenoviral Delivery Of Nos Genes To the Vasculature Have Shosupporting
confidence: 93%
“…In the present study the observed upregulation of HSP 70-1A and -1B is consistent with a previous report showing NO inducing HSP 70 expression in SMC's via HSF 1 activation [27]. It is thought that the upregulation of HSP 70 is to protect the SMC's from injury as a result of NO stimulation [27].…”
Section: Adenoviral Delivery Of Nos Genes To the Vasculature Have Shosupporting
confidence: 93%
“…HSP70, which is one of the most important HSPs ubiquitously distributed in mammalian systems (Schlesinger, 1990;Xu et al, 1997), was expressed by AH136B cells and solid tumours. However, although HSP70 has been reported to be induced by NO exposure (Xu et al, 1997), our present analysis of HSP70 with NO donors and NOS inhibitors in vitro and in vivo showed that NO does not participate in HSP70 upregulation in AH136B cells. Thus, we suggest that HSP70 expression in AH136B tumours may be positively regulated by ischaemia or hypoxia through a mechanism different from HO-1 induction involving NO.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, onset of apoptosis in cells exposed to IFNa was paralleled by HSP increase which was, in turn, neutralized by EGF. These effects can be explained by the finding that HSPs exert an important protective role in the cells against apoptosis induced by several kinds of damaging agents 14,15,27,28 even if their function is still not completely defined. 13,29 Moreover, growth factors can inhibit both spontaneous 10,12 and injury-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In fact, the apoptosis induced by nitric oxyde, a classical shock agent, is prevented by the increased expression of heat shock protein (HSP)-70 in vascular smooth muscle cells. 15 Moreover, it has been reported that a hypoxic stress induces EGF-R upregulation and increases HSP expression in human tumour cells 16 and HSPs themselves confer protection against apoptosis induced by several injuries in cardiocytes and cancer cells. 13,14 Therefore, EGF-R upregulation and stress protein induction could be convergent in the protection from programmed cell death.…”
Section: Introductionmentioning
confidence: 99%